Young females' perceived experience of caring for husbands with stroke. - Drummond K; Pierce LL; Steiner V; Hicks B (Online Journal of Nursing Informatics, 2007)
Purpose: The purpose of this secondary analysis study was to explore young females' perceived experience of caring, as learned from a web-based discussion group, in the first year of their husbands' post-stroke recovery.Method: Narrative email messages from three wives were gathered as part of a larger study that focused on caring. Data (email entries=214) were analyzed and drawn to Friedemann's framework of systemic organization.Findings: Four themes emerged from these data: being social, giving and receiving support, evolving family relationships, and becoming frustrated.Conclusions: These wives focused on doing everything to maintain their systems: self and family [system maintenance in Friedemann's terms]. Additionally, they focused on coherence or feeling connected and pulling together, as they strove for congruence or a balance in their lives.Implications: Nurses can use this information to design or improve holistic interventions for wives new to the role of caring for their husbands with stroke.